Strategic Management of The Principal in The Development of The Pancasila Student Profile Strengthening Project - Rokani, Dewi; Zamroni, M Afif (Journal of Education and Learning Innovation, 2024)
This research utilizes both primary and secondary data sources. The analysis technique used is observation, which includes both source and technical triangulation. The findings indicate that the principal's management strategy in developing the Pancasila student profile project at SMPN 1 Pasekan involves: Strategy Formulation: This process includes defining the school's vision and mission, identifying external opportunities and threats, assessing internal strengths and weaknesses, setting long-term goals, devising alternative strategies, and selecting specific strategies for implementation. Strategy Management Implementation> This step involves the principal preparing a project within an independent curriculum by forming a project team, planning the project, supervising its progress, managing school resources transparently and accountably, and fostering communication and collaboration among parents, students, and project stakeholders. It also includes developing a community of practitioners within the educational unit to enhance educators' skills, providing regular coaching for educators, and planning, implementing, reflecting on, and evaluating projects and student-centered assessments. The principal's role in this initiative includes providing leadership and direction, developing the curriculum, coaching teachers, monitoring and evaluating progress, collaborating with parents and the community, securing resources, promoting awareness, developing educational materials, creating an inclusive environment, measuring impact, addressing challenges, and supporting innovation and creativity.